An advanced cathode composite for co-utilization of cations and anions in lithium batteries. (10th March 2022) - Wang, Xiao-Tong; Yang, Yang; Guo, Jin-Zhi; Gu, Zhen-Yi; Ang, Edison Huixiang; Sun, Zhong-Hui; Li, Wen-Hao; Liang, Hao-Jie; Wu, Xing-Long
Highlights: Hybrid cathode LMFP/G that combined LMFP@C and graphite material was synthesized elaborately. The proposed scheme unlocks and exploits the potential role of anions in the electrolyte adequately. Kinetics property and structural evolution of the hybrid cathode LMFP/G were investigated in detail. Abstract: Anions in the electrolyte are usually ignored in conventional "rocking-chair" batteries because only cationic de-/intercalation is considered. An ingenious scheme combining LiMn0.7 Fe0.3 PO4 (LMFP@C) and graphite as a hybrid cathode for lithium-ion batteries (LIBs) is elaborately designed in order to exploit the potential value of anions for battery performance. The hybrid cathode has a higher conductivity and energy density than any of the individual components, allowing for the co-utilization of cations and anions through the de-/intercalation of Li + and PF6 − over a wide voltage range. The optimal compound with a weight mix ratio of LMFP@C: graphite = 5: 1 can deliver the highest specific capacity of nearly 140 mA h/g at 0.1 C and the highest voltage plateau of around 4.95 V by adjusting the appropriate mixing ratio. In addition, cyclic voltammetry was used to investigate the electrode kinetics of Li + and PF6 − diffusion in the hybrid compound at various scan rates. In situ X-ray diffraction is also performed to further demonstrate the structural evolution of the hybrid cathode during the charge/discharge process. Graphical abstract: Image, graphical abstract In this paper, an exquisite hybrid cathode LiMn0.7 Fe0.3 PO4 @C/G was elaborately designed and synthesized. In the low voltage range (blue line), LiMn0.7 Fe0.3 PO4 @C based on the Li + de-/intercalation mechanism endows the high capacity for hybrid cathode, while the high conductive and cost-effective graphite enables the hybrid cathode possesses high voltage on account of the insertion/ extraction process of PF6 - within the high voltage range (red line). The realization of the perfect synergistic utilization of both cations and anions also points out new direction for the development of conventional lithium battery.